Inkuiri dalam Pengajaran dan Pembelajaran Sains - Misbahul Jannah (Institut Agama Islam Negeri (IAIN) Samarinda, 2020)
Science education is very importance for developing three elements, namely; science concept knowledge, science process skill and scientific attitude. These elements had been a challenge for the pre-service science teachers to study especially in the Indonesia curriculum context. Thus, Pre-service science teachers require implementing science teaching and learning by using inquiry. Inquiry is one of models of teaching which implemented by hands-on dan minds-on. In order to be able to teach science by using inquiry effectively and meaningfully to pre-service science teachers, the lecturer should possess a strong understanding and must exhibit competence in inquiry to be able to effectively teach in their classroom. By using inquiry leads to the suggestion of the enhancement of pre-service science teachers’ science concept knowledge, science process skill and scientific attitude by using inquiry based learning.